Influence of notch constraint on creep damage evolution and rupture life of grade 91 steel - Imam, Ul Ferdous (2022)
Coal-fired power plants must operate at higher temperatures and pressures to achieve maximum efficiency. During operation, components are exposed to a creep environment that can lead to catastrophic failure. Predicting the creep rupture life of high-temperature steel components requires hours of robust long-term testing over a range of stresses and temperatures. Considerable effort has been made to develop alternative methods that reduce the time and cost of testing. In fact, components are usually under a multiaxial state of stress due to irregularities caused by curvatures, edges, and notches. The present work focused on evaluating the creep behaviour, the effect of notch constraint on creep damage and rupture life, and the development of a prediction model of Grade 91 steel. Creep tests were performed on smooth and notched specimens having the acuities of 2.28 and 4.56. The tests were conducted at 600 °C under different stress levels ranging from 160 MPa to 190 MPa for smooth specimens and from 210 MPa to 240 MPa for notched specimens. In addition, finite element analysis was performed in conjunction with the strain-based ductility exhaustion model to predict the creep rupture life and damage evolution under the influence of different stress states. Due to the limited data obtained from the experiment, additional data from the literature were used to formulate the constitutive material and damage model incorporating Monkman-Grant ductility. The reduction in ductility induced by the notch was estimated using the Cock and Ashby void growth model. The creep curve obtained from the creep tests shows all three stages, termed primary, secondary, and tertiary, for both specimens. The secondary stage appears to be dominant in all three stages. Analysis of creep life under the influence of net stress showed that the notched specimen had a longer creep life than the smooth specimen at the same stress level, indicating a "notch strengthening" effect. The von-Mises stress was found to control the rupture life. Fractographic examination exposed that ductile dimples predominated in the smooth specimen. For the notched specimen, as the notch acuity increased, the region adjacent to the notch showed shallow dimples, indicating less plasticity and limited creep deformation. Furthermore, the rupture time calculated by finite element analysis also showed good agreement with the experimental data for both short- and long-term creep regimes. All the rupture time data fall within the ± factor of 2. It was also found that the location of damage initiation is strongly influenced by the triaxiality and equivalent creep strain. This location was consistent with the lower plasticity region on the rupture surface of the crept sample during the fractography examination. In conclusion, the presence of a notch affects the creep deformation, damage, and rupture life of Grade 91 steel. The proposed model proves to be adequate for predicting the creep life at different notch acuities. An effort has been made to develop a stress-based prediction model based on Norton's power law to predict the creep rupture life under the influence of multiaxial-stress states. Comparison of the experimental results with the finite element analysis and Norton's power law shows a good agreement. In conclusion, the presence of a notch affects the creep deformation, damage, and rupture life of Grade 91 steel. The proposed model proves to be adequate for predicting the creep life at different notch acuities.